Comparison between self-reported and accelerometer-derived measurements for classifying children and adolescents as physically active in Chile - Nicolas Aguilar-Farias; Sebastian Miranda-Marquez; Marcelo Toledo-Vargas; Damian Chandia-Poblete (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
The aim of this study was to compare self-reported with two accelerometer-derived methods to classify Chilean children and adolescents as physically active. In total, 247 students wore an accelerometer on their hips during 7 consecutive days to classify them as physically active based on (1) daily accumulation of ≥ 60 minutes of moderate-to-vigorous physical activity (MVPA) on each of the seven days, and (2) average MVPA ≥ 60 minutes/day. Also, participants were classified as physically active if they reported being active for at least 60 minutes in all seven days. When using the accelerometer data, 0.8% were active in all seven days, while 10.5% recorded ≥ 60 minutes MVPA per day on average. Based on self-report, 7.2% were physically active. The agreement between self-reported and accelerometer estimations were poor. Important differences were observed between the self-reported and device-derived methods for classifying children and adolescents as physically active. When comparing them, some considerations should be taken. The findings suggest that these methods are not interchangeable. Therefore, if possible, they should be used as complementary measurements.